Pengaruh Model Latihan Menggunakan Pelampung dan Panjang Tungkai terhadap Hasil Kecepatan Renang Gaya Dada 50 M Atlet Renang Tiara Swimming Club Kabupaten Jepara - Nugroho, Eko Wahyu; Raharjo, Hermawan Pamot; Putra, Ranu Baskora Aji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to determine the effect of using flotation devices on the results of 50-meter breaststroke swimming training and to identify the differences in the impact of thigh length categories (high, medium, and low) on the results of 50-meter breaststroke swimming training for beginner athletes of KU IV Tiara Swimming Club, Jepara Regency. The research method is experimental with a 3x3 design, involving a sample of 29 beginner athletes. Those with the highest and lowest pretest results were excluded, resulting in a sample of 27 beginner athletes from KU IV selected through purposive sampling. The instrument for the test is to provide training treatment using a pull buoy float, fishing net, and board. Related to the length of the thigh category: high, medium, and low. The research results show (1) there is a significant difference in the outcomes for students using pull buoy floats, fishnet floats, or boards in the 50-meter breaststroke swimming practice. (2) There are significant differences in results for students with high, medium, or low leg lengths in the 50-meter breaststroke training. (3) There is no interaction between leg length and type of buoy in determining the results of the 50-meter breaststroke training. Conclusion: The fishnet float yielded more significant results compared to using the board float and pull buoy, as evidenced by an average result of 56.67 seconds, compared to the pull buoy float at 72.33 seconds and the board float at 72.33 seconds. The thigh length in the high category yielded more significant results compared to the medium and low thigh length categories. There was no interaction between thigh length and buoy type on the results of the 50-meter breaststroke swimming speed. Keywords: Buoy, leg length, breaststroke swimming speed